The representation of likeability in American pop culture: A case study of Clueless (1995) - Prasetyo, Nikken; Muna, Nailil (Lembaga Penelitian, Penerbitan, Pengabdian dan Pengembangan Masyarakat (LP4M) Unmuha, 2025)
Teenage popularity is often portrayed negatively in American pop culture, frequently associated with bullying, beauty privilege, and social exclusion. This study offers an alternative perspective by applying Mitch Prinstein’s theory of likeability, which frames popularity as an indicator of strong interpersonal relationships and high social acceptance. This perspective is captured in Amy Heckerling’s Clueless (1995), particularly its depiction of the